Psychological Features Of The Development Of Communicative Skills In Students In The Direction Of Pedagogy (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This article explores the psychological features of developing communicative skills in students, specifically those pursuing studies in pedagogy. The importance of effective communication in the educational field is emphasized, and the article examines the psychological processes and factors that influence the development of these skills. The study investigates both the theoretical and practical aspects of communication in pedagogy, offering methods and strategies for enhancing communicative competence in future educators